Tooth auto‐transplantation: A bibliometric analysis of the top 100 most‐cited articles - Ahmed Abdou (14779309) (2023)
Background/Aim Tooth auto-transplantation has recently gained high clinical acceptance. The aim of this study was to identify the top 100 most-cited articles regarding tooth auto-transplantation, to analyse multiple citations and publication metrics and to outline the historical scientific advancements in this field. Materials and Methods An advanced search of the Clarivate Analytics' Web of Science ‘Core Collection’ and Elsevier's Scopus databases utilising specific keywords related to tooth auto-transplantation between 1971 and 2021 was performed. The retrieved articles were ranked in descending order based on their Web of Science citation counts and further cross-matched with citation data from Scopus. The extracted data included citation counts, citation density, level of evidence, year of publication, contributing authors names and institutes, corresponding author's address, journal of publication, journal local citations index, cumulative growth index, keywords and keywords Plus. Data analysis was performed using descriptive statistics and graphical mapping. Results A total of 1290 articles were retrieved. The top 100 most-cited articles received a total of 4899 (Web of Science) and 5250 (Scopus) citations. Among these, cohort studies (29%) and case series (18%) were the most common study designs. Scandinavian countries produced major contributions in defining the top 100 most-cited articles and ranked within the top 5 countries based on the number of publications and citations per year. The greatest contributing authors were Schwartz O (n = 12), Andreasen JO (n = 8) and Paulsen HU (n = 6), and they were affiliated with Copenhagen, Denmark. The top contributing journals were American Journal of Orthodontics and Dentofacial Orthopedics, International Journal of Oral and Maxillofacial Surgery, Oral Surgery Oral Medicine Oral Pathology Oral Radiology, European Journal of Orthodontics, Dental Traumatology and Journal of Oral and Maxillofacial Surgery. Conclusion This bibliometric analysis revealed a large geographical scientific interest and broad development in the field of tooth auto-transplantation spanning multiple dental disciplines. Other Information Published in: Dental Traumatology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1111/edt.12779